The Ambivalence of Identity in Tope Folarin's A Particular Kind of Black Man (2019) - Tiara Agnesi Windari; Desvalini Anwar (Universitas Negeri Padang, 2023)
This study examined how the novel A Particular Kind of Black Man (2019) by Tope Folarin portrayed the issue of ambivalent identity. The main character named Tunde Akinola is a second-generation immigrant who experiences ambivalence of identity. This analysis is related to the concept of ambivalence and mimicry by Homi K. Bhaba. Researchers use those theories to interpret the hidden meaning of the novel. The data collection is in the form of sentences, and paragraphs from the novel. For this study, the researcher use the qualitative method by connecting the sentence and paragraph to many journals, books,s and also podcasts. The result is the factor's ambivalent identity of the main character is caused by the parent’s broken American dream and also the racism he gets because he is Black. Because of the racism, the main character concludes that he is not American because he is not White, and determined to be the perfect Black Man by mimicking many successful Black Men. The main character becomes sick of faking to be something he is not and finally embraces his identity as a hybrid.